2022
DOI: 10.7554/elife.81679
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty alters the balance between incremental learning and episodic memory

Abstract: A key question in decision making is how humans arbitrate between competing learning and memory systems to maximize reward. We address this question by probing the balance between the effects, on choice, of incremental trial-and-error learning versus episodic memories of individual events. Although a rich literature has studied incremental learning in isolation, the role of episodic memory in decision making has only recently drawn focus, and little research disentangles their separate contributions. We hypoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…how drastically context is shifted to reflect each new sample), the agent can modulate its reliance on temporal abstraction vs constructive, rollout-based simulation, allowing it to balance the costs and benefits of these evaluation regimes depending on circumstances. This is similar to other examples in which, it has been argued, the brain adjusts its decision computations due to similar cost-benefit tradeoffs (Daw, Niv, & Dayan, 2005;Keramati, Dezfouli, & Piray, 2011;Nicholas, Daw, & Shohamy, 2022).…”
Section: Data From Free Recall Experiments Suggest An Intermediate Re...supporting
confidence: 86%
See 1 more Smart Citation
“…how drastically context is shifted to reflect each new sample), the agent can modulate its reliance on temporal abstraction vs constructive, rollout-based simulation, allowing it to balance the costs and benefits of these evaluation regimes depending on circumstances. This is similar to other examples in which, it has been argued, the brain adjusts its decision computations due to similar cost-benefit tradeoffs (Daw, Niv, & Dayan, 2005;Keramati, Dezfouli, & Piray, 2011;Nicholas, Daw, & Shohamy, 2022).…”
Section: Data From Free Recall Experiments Suggest An Intermediate Re...supporting
confidence: 86%
“…Additionally, other manipulations that affect memory, like proactive and retroactive interference, should also have concomitant effects on decisions via enhancement or suppression of particular states and/or outcomes. Conversely, the rationalization of these parameterized memory effects as enabling more efficient choice in various settings suggests that the parameters governing them are potentially malleable, adapting to the statistics of the study material to optimize choice (Nicholas et al, 2022). For instance, when states or study items reflect non-reversible environmental dynamics, a rational RL agent would be expected to dial back the reversibility assumption when learning an SR.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Finally, recent modeling work has shown that the relative influence of procedural and episodic memory on decision making (see Figure 5b) varies as a function of environmental uncertainty and that this balance may be related to (mal)adaptive choice (Nicholas et al, 2022). As EDs are characterized by greater intolerance of uncertainty (Kesby et al, 2017), similar research in this population may prove meaningful.…”
Section: Moving Forward: Integrating Memory Research In Edsmentioning
confidence: 85%
“…Crucially, each strategy is associated with a different profile of cognitive resource use. Keeping track of individual experiences is much costlier than tracking a single expectation and a confidence interval around it 52,53 and more likely to incur costs when switching between exploring different tables. Prior work suggests individuals switch between using single experiences and summary statistics according to the reliability of each strategy, and the cost of using it 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Keeping track of individual experiences is much costlier than tracking a single expectation and a confidence interval around it 52,53 and more likely to incur costs when switching between exploring different tables. Prior work suggests individuals switch between using single experiences and summary statistics according to the reliability of each strategy, and the cost of using it 52,53 . In our case, summary statistics may be perceived as unreliable when overall uncertainty is high, compelling participants to rely on committing individual experiences to working memory 47,50,52,54,55 .…”
Section: Discussionmentioning
confidence: 99%